Same-Day Discharge after Non-Perforated Laparoscopic Appendectomy Is Safe - Areg Grigorian; Catherine M. Kuza; Sebastian D. Schubl; Ninh T. Nguyen; Christian de Virgilio; Dennis Kim; Michael Lekawa; Jeffry Nahmias (Journal of Investigative Surgery, 2021)
Purpose: Several single-center studies have demonstrated same-day discharge (SDD) to be safe in adults undergoing laparoscopic appendectomy (LA) for non-perforated appendicitis (NPA). The proportion of SDD appendectomy patients nationally is unknown. We sought to identify the incidence of SDD among patients undergoing LA after NPA hypothesizing a similar risk of complications including superficial surgical site infections (SSSIs), post-operative intra-abdominal abscess, and 30-day readmission rates. Materials and methods: The 2016–2017 ACS-NSQIP Procedure-Targeted Appendectomy database was queried for adults undergoing LA with no intraoperative findings of perforation or abscess. Patients with SDD were compared to those discharged within two days. A multivariable logistic regression model was used for analysis. Results: From 16,931 patients undergoing LA, 3988 (23.6%) were SDD. Compared to those with a longer hospital stay, patients with SDD were of similar age (p = 0.29) and less likely to have a contaminated wound-class (58.5% vs. 62.6%, p < 0.001). After adjusting for age and comorbidities, patients with SDD had a similar risk of 30-day readmission (p = 0.088) and post-operative abscess (p = 0.739) but lower risk of SSSI (OR: 0.48, 0.28–0.82, p = 0.008), compared to those discharged within two days. Conclusions: Nearly a quarter of patients with NPA undergoing LA are discharged the same day. The risk of 30-day readmission is similar compared to those with a longer index hospital stay. Interestingly, the risk of SSSI is lower, however this may be related to differences in wound classification and/or selection bias. Regardless, SDD for NPA patients appears safe and should be utilized whenever possible.